A Statistical Approach of the Flexural Strength of PLA and ABS 3D Printed Parts - Zisopol, D. G.; Nae, I.; Portoaca, A. I.; Ramadan, I. (Engineering, Technology & Applied Science Research, 2022)
The need for rapid obtaining parts has made researchers to widely study 3D common printing technologies like FDM (Fused Depositing Modeling), SLS (Selective Laser Sintering), SLA (Stereolithography). Although FDM can provide high geometrical complexity of parts at convenient costs and with efficient delivery logistics, a set of printing parameters of the raw materials used for manufacturing needs to be optimized accordingly. Therefore, this study reveals the influence of printing parameters on the flexural strength of PLA (Polylactic Acid) and ABS (Acrylonitrile Butadiene Styrene) printed samples, by applying the Taguchi method and ANOVA (Analyisis of Variance) of 3-point bending tests results.